Information system design for alumni of Ma Chung University's information systems study program - Renny Diana Syafitri (Department of Information Technology, Universitas Timor, Indonesia, 2022)
The Alumni Information System is needed to help and make it easier to manage alumni data, a forum for communication between alumni and study programs, alumni and lecturers, alumni with alumni themselves, and alumni with their younger siblings (active students). So this research was made to help solve the problems of the Ma Chung University Information Systems Study Program to manage data and maintain close familial relationships between alumni and study programs.